PERANCANGAN APLIKASI CAPTURE TRAFFIC NETWORK TCP/IP MENGGUNAKAN NODE.JS BERBASIS WEB - Mody Unedo Ritonga; Naiksin Fandier Saragih; Asaziduhu Gea (Universitas Methodist Indonesia, 2020)
With more and more people accessing the internet to get information and the absence of settings on data traffic it will cause the network to be slow. The network traffic settings in Linux Ubuntu still use scripts that are relatively more difficult to use and understand for some people, so tools are needed to configure them. Capture network traffic application is Software designed to capture communications connected to servers. Capture network traffic application can only log data and read TCP/IP and HTTP protocols. The Capture network traffic application has various features, including checking whether the server is on or off, capturing traffic packets on a LAN network, and displaying a map of the URL location. So the results of this study explain the creation of a Traffic Management Configurator to facilitate traffic monitoring settings in gateways that connect different networks. Furthermore, this traffic monitoring application is used to view the actual packets of traffic on the network and network statistics. Both applications use the web as an interface to the user.